Permasalahan Korupsi, Kolusi, dan Nepotisme di Daerah serta Strategi Penanggulangannya - Ismansyah, Ismansyah; Sulistyo, Purwantoro Agung (Jurnal Demokrasi, 2010)
Corruption, Collusion, and Nepotism in Indonesian is no more representing a phenomenon, but this have been representing factually which is famous everywhere. However, KKN (Corruption, Collusion, and Nepotism) will be shares that are not dissociated from bureaucrat government system. Nowdays, KKN (Corruption, Collusion, and Nepotism) many cases in Indonesian, but there are not strategy of problem. This article will try explaining Good Governance and strategy of problem Corruption, Collusion, and Nepotism. Kata Kunci: Good Governance, strategy of problem, Corruption, Collution, Nepotism